Anointed or appointed? Father–daughter succession within the family business. (September 2021) - McAdam, Maura; Brophy, Martina; Harrison, Richard T
With the focus on events and outcomes shaping most of the existing family business research on intra-family succession, the subtleties of the incumbent–successor relationship and the dynamic nature of succession as a process of becoming is somewhat neglected. In particular, we have limited understanding of how successor identities are constructed as legitimate between incumbent and successor during father–daughter succession. This article addresses this gap in understanding by exploring how the daughter successor engages in identity work with the father incumbent during the process of succession and the role of father–daughter gendered relations in shaping her successor identity. Using a two-stage research design strategy, we draw upon empirical evidence derived from 14 individual and joint semi-structured interviews to present a narrative analysis of five father–daughter dyads. In so doing, we unveil how the daughter's successor identity was co-constructed as legitimate and how father–daughter gendered relations influenced this process. Although daughters rely on certain father–daughter relations (preparation, endorsement and osmotic credibility) for legitimacy, they also need to develop independently of their father to heighten their own visibility and establish credibility.